2009
DOI: 10.1002/humu.20845
|View full text |Cite
|
Sign up to set email alerts
|

Functional, structural, and genetic evaluation of 20CDKN2Agerm line mutations identified in melanoma-prone families or patients

Abstract: Germline mutations of the CDKN2A gene are found in melanoma-prone families and individuals with multiple sporadic melanomas. The encoded protein, p16INK4A , comprises four ankyrin-type repeats, and the mutations, most of which are missense and occur throughout the entire coding region, can disrupt the conformation of these structural motifs as well as the association of p16INK4a with its physiological targets, the cyclin-dependent kinases (CDKs) CDK4 and CDK6. Assessing pathogenicity of nonsynonymous mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 61 publications
8
57
0
Order By: Relevance
“…For example, missense mutations or deletions of the INK4/ARF locus represent the most important alterations in familial melanoma (41% of cases) (Orlow et al, 2007;Kannengiesser et al, 2009). Furthermore, in families with BRCA2, MMR genes and INK4/ARF locus mutations, there is an increased risk of cutaneous melanoma, acute lymphatic leukemia and blast leukemia in childhood (Magnusson et al, 2008;Daniotti et al, 2009).…”
Section: Other Functions Attributed To P16 Ink4amentioning
confidence: 99%
“…For example, missense mutations or deletions of the INK4/ARF locus represent the most important alterations in familial melanoma (41% of cases) (Orlow et al, 2007;Kannengiesser et al, 2009). Furthermore, in families with BRCA2, MMR genes and INK4/ARF locus mutations, there is an increased risk of cutaneous melanoma, acute lymphatic leukemia and blast leukemia in childhood (Magnusson et al, 2008;Daniotti et al, 2009).…”
Section: Other Functions Attributed To P16 Ink4amentioning
confidence: 99%
“…We screened for point mutations in CDKN2A (exons 1a, 2, and 3), adenosine diphosphate-ribosylation factor (ARF) (exon 1b), and CDK4 (exon 2) using denaturing high-performance liquid chromatography or direct sequencing as described previously. 28,29 Genomic deletion screening of the CDKN2A locus also was carried out as described previously. 30 …”
Section: Cdkn2a and Cdk4 Mutation Testingmentioning
confidence: 99%
“…A recent study on a series of CDKN2A missense variants, however, showed potential limits of these approaches: widely conflicting results, in fact, were obtained, with several specific variants, that were paradoxically predicted to be benign or pathogenic, depending on the software used (Kannengiesser et al, 2009). Undoubtedly, in silico approaches provide an excellent support for UVs classification, but their accuracy is apparently limited by the available evolutionary, mutational or structural databases and, in some cases, by intrinsic limitations of each individual method.…”
Section: Indirect Evidence Of Pathogenicity: In Silico Analysismentioning
confidence: 99%
“…A powerful assay must be designed according to the functional properties of the encoded protein and hence each single cancer-predisposing gene requires the development of a set of specific tests. A variety of p16 missense variants were investigated by functional analysis (Kannengiesser et al, 2009;McKenzie et al, 2010;Ruas et al, 1999), since two main p16 functions can be easily measured in vitro: the CDK4/6 binding capacity and the p16 ability to arrest cellcycle. In particular, the advantage of using cell growth inhibition assays is that they evaluate a phenotype directly involved in tumorigenesis.…”
Section: Indirect Evidence Of Pathogenicity: Functional Analysismentioning
confidence: 99%
See 1 more Smart Citation